A Stunting Risk Model Based on Children's Parenting Style - Mayang Sari Ayu; Meri Susanti; Tezar Samekto Durungan (PT Inovasi Pratama Internasional, 2023)
The Global Nutrition Report (2020) stated that stunting is a nutrional problem in children and there are 7,8 million stunted children out of 23 million children in the world. The prevalence of stunting in Indonesia is 24.4%. WHO targeted less than 20% stunting cases in 2024 globally. Parenting styles for toddlers contribute to stunting. Toddlers immunization status and the exclusive breast-feeding are examples of parenting styles. This study aimed to analyze risk factors influencing stunting based on parenting. Case Control approach was used in this study. The sample was taken by using purposive sampling and mothers have stunted 1-5 years old children as case group). Comparison Ratio 1:1 with the control group. Statistical analysis was carried out using the chi-square test (2x2), with an expected value of more than 20%, the Fisher's exact test is used.Multivariate analysis with logistic regression analysis, measuring the effect of a namely the stunting risk assessment.The nominal scale 2 categories, stunting and not stunting. Risk factors of stunting resulted from logistic regression analysis (p>0.05) are nutritional status, exclusive breastfeeding, complementary feeding, immunization status, infectious diseases, and low birth weight. Stunting can be stopped by improving child feeding, improving women's nutrition and household sanitation.